Kekuatan Tarik yang Dipengaruhi Arah Susunan dan Fraksi Volume Serat Pelepah Nipah Pada Komposit Serat - Rizki, Muhammad; Erwansyah, Erwansyah; Idiar, Idiar (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Nipa plant is a plant that can be found in water areas such as in swamps. Quite a lot that can be utilized from this swamp plant. Utilization of the nipa plant can be sourced from its fruit, midrib, and leaf bones [1]. In addition to the uses previously described, the nipa plant in its midrib has fiber which has been extensively researched on this fiber. Nipa midribs which have fibers can be used as reinforcement for fiber composites. This study aims to determine the effect of arrangement and volume fraction of fibers that have been determined, as well as knowing whether the use of nipa midrib fiber as a composite reinforcement material can or cannot achieve the tensile strength value of the high impact ABS plastic material on the car dashboards. The research method in this study uses factorial design with manual composite printing. The results of this study were that the highest value of the tensile strength of the nipa midrib fiber composite was found in the vertical arrangement direction with a volume fraction 15%, namely 26.43 MPa, while the lowest value is found in the direction of horizontal arrangement with a volume fraction of 15%, namely 14.07 MPa. So that the value of the nipa midrib fiber composite in the vertical arrangement direction with a volume fraction of 15% achieves the tensile strength value of the high impact ABS plastic material on the car dashboards, namely 20 – 40 MPa.